Liquid biopsy as a diagnostic and prognostic tool for women and female dogs with breast cancer - Colombo, Jucimara; Moschetta-Pinheiro, Marina Gobbe; Novais, Adriana Alonso; Stoppe, Bruna Ribeiro; Bonini, Enrico Dumbra; Gonçalves, Francine Moraes; Fukumasu, Heidge; Coutinho, Luiz Lehmann; Chuffa, Luiz Gustavo de Almeida [UNESP]; Zuccari, Debora Aparecida Pires de Campos (MDPI, 2021)
Introduction: Breast cancer (BC) is the malignant neoplasm with the highest mortality rate in women and female dogs are good models to study BC. Objective: We investigated the efficacy of liquid biopsy to detect gene mutations in the diagnosis and follow-up of women and female dogs with BC. Materials and Methods: In this study, 57 and 37 BC samples were collected from women and female dogs, respectively. After core biopsy and plasma samples were collected, the DNA and ctDNA of the tumor fragments and plasma were processed for next generation sequencing (NGS) assay. After preprocessing of the data, they were submitted to the Genome Analysis ToolKit (GATK). Results: In women, 1788 variants were identified in tumor fragments and 221 variants in plasma; 66 variants were simultaneously detected in tumors and plasma. Conversely, in female dogs, 1430 variants were found in plasma and 695 variants in tumor fragments; 59 variants were simultaneously identified in tumors and plasma. The most frequently mutated genes in the tumor fragments of women were USH2A, ATM, and IGF2R; in female dogs, they were USH2A, BRCA2, and RRM2. Plasma of women showed the most frequent genetic variations in the MAP3K1, BRCA1, and GRB7 genes, whereas plasma from female dogs had variations in the NF1, ERBB2, and KRT17 genes. Mutations in the AKT1, PIK3CA, and BRIP genes were associated with tumor recurrence, with a highly pathogenic variant in PIK3CA being particularly prominent. We also detected a gain-of-function mutation in the GRB7, MAP3K1, and MLH1 genes. Conclusion: Liquid biopsy is useful to identify specific genetic variations at the beginning of BC manifestation and may be accompanied over the entire follow-up period, thereby supporting the clinicians in refining interventions.
Keywords: Breast cancer; Circulating tumor DNA (ctDNA); Gene variant; Liquid biopsy; Next generation sequencing (NGS)